The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.15252/embr.201744228
|View full text |Cite
|
Sign up to set email alerts
|

Cold stress‐induced ferroptosis involves the ASK 1‐p38 pathway

Abstract: A wide variety of cell death mechanisms, such as ferroptosis, have been proposed in mammalian cells, and the classification of cell death attracts global attention because each type of cell death has the potential to play causative roles in specific diseases. However, the precise molecular mechanisms leading to cell death are poorly understood, particularly in ferroptosis. Here, we show that continuous severe cold stress induces ferroptosis and the ASK1-p38 MAPK pathway in multiple cell lines. The activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 55 publications
(80 reference statements)
2
90
0
Order By: Relevance
“…These findings indicate that the molecular mechanism of cold stress-triggered liver graft damage was likely to be distinct from apoptosis, necrosis, or necroptosis. Since recent reports have demonstrated tissue-specific importance of ASK1/ p-p38 signaling in cold-stress cell damage (10,11), we focused on the ASK1/p-p38 axis in our model. Interestingly, the markedly increased hepatic ASK1 and p-p38 expression seen after cold storage (4°C/18 hours) in WT livers decreased in OLT at 3 hours after reperfusion ( Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that the molecular mechanism of cold stress-triggered liver graft damage was likely to be distinct from apoptosis, necrosis, or necroptosis. Since recent reports have demonstrated tissue-specific importance of ASK1/ p-p38 signaling in cold-stress cell damage (10,11), we focused on the ASK1/p-p38 axis in our model. Interestingly, the markedly increased hepatic ASK1 and p-p38 expression seen after cold storage (4°C/18 hours) in WT livers decreased in OLT at 3 hours after reperfusion ( Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis signal-regulating kinase 1 (ASK1), a member of the MAP3K family, becomes activated by a wide range of extra-and intracellular stressors. Activation of p38 MAPK was reported in cold-induced tissue injury (9,10), whereas a recent study has identified tissuespecific contribution of ASK1 and p-p38 pathways in cell death signaling (11). The role of the ASK1/p-p38 axis in the mechanism of liver transplant damage has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a newly discovered form of regulated cell death that plays a major role in various diseases, including tumor, stoke, cold stress, acute kidney failure, and neural degeneration. 13,18,[29][30][31][32] As in TBI, a recent study reported that ferroptotic death possibly occurs at early time points after TBI in the pediatric rat CCI model due to elevated levels of 15-HpETE-PE in the brain cortex and hippocampus, along with increased expression of 15LO2 and decreased levels of GPX4. 19 However, the precise role of ferroptosis in adult rodents remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into consideration that the MAPK signaling pathway, including ERK, p38, and c-JUN NH 2 -terminal kinase (JNK) is involved in the execution of ferroptosis in other cells (10, 49), we evaluated whether co-exposure to DHT and INS may be linked to activation of the MAPK signaling pathway in the gravid uterus and placenta. As shown in Figure 4A , in the gravid uterus DHT+INS exposure resulted in an increased abundance of phosphorylated ERK1/2 (p-ERK1/2) and decreased total ERK1/2, which subsequently resulted in an increased p-ERK1/2:ERK1/2 ratio.…”
Section: Resultsmentioning
confidence: 99%